2017
DOI: 10.1016/j.stemcr.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial SCA-1 + Progenitor Cell Gene Sequencing Reveals the Mechanisms of Cell Migration in Response to Hyperlipidemia

Abstract: SummaryAdventitial progenitor cells, including SCA-1+ and mesenchymal stem cells, are believed to be important in vascular remodeling. It has been shown that SCA-1+ progenitor cells are involved in neointimal hyperplasia of vein grafts, but little is known concerning their involvement in hyperlipidemia-induced atherosclerosis. We employed single-cell sequencing technology on primary adventitial mouse SCA-1+ cells from wild-type and atherosclerotic-prone (ApoE-deficient) mice and found that a group of genes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 65 publications
2
26
0
Order By: Relevance
“… 119 In addition, apolipoprotein E–deficient (ApoE −/− ) mice, which model atherosclerosis, have elevated numbers of Sca-1 + cells in the aortic endothelium. 120 Hu et al 26 demonstrated that adventitia-resident vascular progenitor cells express Sca-1 and that these cells contributed to atherosclerosis via migration and differentiation into SMCs. Among other studies, the work of Yu et al 121 further supported the notion that resident Sca-1 + cells contribute to neointima formation, which may increase plaque burden.…”
Section: Vascular Resident Stem Cells In Adultsmentioning
confidence: 99%
“… 119 In addition, apolipoprotein E–deficient (ApoE −/− ) mice, which model atherosclerosis, have elevated numbers of Sca-1 + cells in the aortic endothelium. 120 Hu et al 26 demonstrated that adventitia-resident vascular progenitor cells express Sca-1 and that these cells contributed to atherosclerosis via migration and differentiation into SMCs. Among other studies, the work of Yu et al 121 further supported the notion that resident Sca-1 + cells contribute to neointima formation, which may increase plaque burden.…”
Section: Vascular Resident Stem Cells In Adultsmentioning
confidence: 99%
“…Furthermore, lipid loading increased adventitial metalloproteinase-9 levels to promote cell migration. 30 Intriguingly, we found that HHcy induced AFs migration and invasion in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, lipid loading increased adventitial metalloproteinase-9 levels to promote cell migration. 30 Intriguingly, we found that HHcy induced AFs migration and invasion in vitro and in vivo. Telmisartan also inhibited the migration and invasion of broblasts induced by HHcy (Figs.…”
Section: Discussionmentioning
confidence: 68%